(untitled) (translation. a transdisciplinary journal, 2022)
The Caucasian Chalk Circle is one of the most important works of the German playwright Bertolt Brecht ( 1 898-1956). It is also one of the most widely performed modern plays in the West. However, this critically acclaimed play is not purely Brecht’s "originality" but is indebted to an ancient Chinese play, Li Xingdao’s Hui Lan (The Story of the Circle of Chalk). ’ Brecht acknowledged his adaptation in the prologue of The Caucasian Chalk Circle in the voice of the singer: "It is called ’The Chalk Circle’ and comes from the Chinese. But we’ll do it, of course, in a changed version" ( Brecht 1983, 1 26).